Konsep diri, kematangan emosi, dan perilaku bullying pada remaja - Nurul Aulina (Fakultas Psikologi, 2019)
Bullying behavior is an act of violence committed to harm other people. Bullying behavior can be reduced or controlled by the existence of positive psychological variables, namely self-concept and emotional maturity. The aim of the study is to know, dig, review and organize theoretical and empirical information about self-concept relationships, emotional maturity with bullying behaviour in adolescents. Self-concept, emotional maturity, and bullying behavior studied in 150 early adolescents with an age range of 12 – 15 years. This research is a quantitative study with a partial correlation design and sampling techniques used is the sampling of quotas. The results showed no relation between self-concept and bullying behavior when the maturity of emotions was controlled (r = -0.040; p = 0.625).